Woman, hypertension and childbearing age: the role of androgens in this complex problem (Boletin Médico de Postgrado, 2022)
Hypertension is the result of a complex interplay of environmental and pathophysiological factors that affect multiple physiological systems, being genetic predisposition and sexual differences some of the fundamental determinants of blood pressure control. Hypertension in woman of childbearing age represents a challenge due to its high prevalence, complex mechanism, androgens participation and the presence of polycystic ovary syndrome in some clinical situations as a final way of this hormonal unbalance. The following review describes the physiopathological mechanisms involved in the development of hypertension in women of child bearing age.
Keywords: women; hypertension; androgens; fertile period; prevalence